Mediating Mechanisms of Perfectionism: Clinical Comorbidity of OCD and ED - Reivan Ortiz, Geovanny Genaro; Rivera Tapia, Cristhian Javier; Elizalde Martínez, Braulio Andrés; Icaza, Daniel (Frontiers in Psychiatry, 2022)
Obsessive-Compulsive Disorder (OCD) and Eating Disorders (ED) share common causal factors and often represent similar entities. Studies on the relationship between perfectionism, obsessive-compulsive traits and eating disorders reveal a significant correlation between maladaptive perfectionism. The aim of this study is to assess the predictive variables of perfectionism in patients diagnosed with Anorexia Nervosa (AN), Bulimia Nervosa (BN) and OCD using a structural model. Findings uncover that the model is equal across the disorders assessed from diagnosed patients. Future studies are encouraged to address subtypes of the assessed disorders with longitudinal designs.